Characteristic of Pulp and Paper made from Middle section of Betong Bamboo (Dedrocalamus Asper) by soda pulping method - Farid Zulhilmi Amri; Shaiful Rizal Masrol (Progress in Engineering Application and Technology, 2022)
This study has been carried out to investigate the characteristics of pulp and paper produced from Malaysian bamboo. Middle section of Betong Bamboo (Dendrocalamus asper) has been selected as the main raw papermaking material. 120 gsm paper sheet of bamboo has been prepared from unbeaten and unbleached bamboo Soda pulp. The evaluation of the pulping process has been studied based on the chemical. Sodium Hydroxide (NaOH) with dosage of 25% has been used in soda pulping process. The Malaysian International Organization for Standardization (MS ISO) and the Technical Association of the Pulp and Paper Industry (TAPPI) were cited as standards for all process and characteristic tests. Pulp moisture content(20.97%), screen yield percentage (20.59%), pulp drainage time (5.772s), and Canadian Standard Freeness (CSF) have all been observed (725ml). Thickness (598.9μm), grammage (126.1 gsm), and paper density (0.212 g/cm3) were measured as physical characteristics. Tensile index (10.76 Nm/g), tear index (1.32 mN.m2/g), burst index (1.541 kPa.m2/g), and folding endurance were also investigated (1.111). This research was demonstrate the potential characteristics of middle section of Betong bamboo as a newly explored non-wood based raw material for papermaking.